La Belle : The Archaeology of a Seventeenth-Century Vessel of New World Colonization - Ray, Eric D.; Jones, Bradford M.; Borgens, Amy; Bruseth, James E. (Book collections on Project MUSE., 2017)
The complete technical and scientific report on one of the most important shipwrecks in North American history ... In 1995, Texas Historical Commission underwater archaeologists discovered the wreck of the La Salle's La Belle, remnant of an ill-fated French attempt to establish a colony at the mouth of the Mississippi River but landing instead along today's Matagorda Bay in Texas. For the next two years, the Commission uncovered the ship's remains under the direction of archaeologist James E. Bruseth and employing a team of archaeologists and volunteers. Amid the shallow waters of Matagorda Bay, a steel cofferdam was constructed around the site, creating one of the most complex nautical archaeological excavations ever attempted in North America and allowing the archaeologists to excavate the sunken wreck much as if it were located on dry land. The ship's hold was discovered full of everything the would-be colonists would need to establish themselves in the New World; more than 1.6 million artifacts were recovered from the site. More than two decades in the making due to the immensity of the find and the complexity of cataloging and conserving the artifacts, this book thoroughly documents one of the most significant North American archaeological discoveries of the twentieth century.